The Relationship of Muzakki to Increasing Individual Welfare: Analysis at Baznas Tanjungpinang City - Bintania, Aris; Hantoro, Ramandha Rudwi; Layla, Muslena (SCAD Independent, 2024)
Every human wants his life to be prosperous because one’s welfare is the characteristic of happiness. Welfare is even a benchmark for the stability of a country. From the Islamic perspective, one way to achieve welfare is to pay zakat. This article describes the relationship of muzakki to increasing individual welfare. The method used in this research is quantitative. The population of this study was non-ASN muzakki, who were registered at the Badan Amil Zakat Nasional (BAZNAS) of Tanjungpinang City as many as 200 muzakki. One hundred thirty-two (132) people were sampled; however, because the method used was purposive sampling, only 44 people were sampled and carried out randomly. The results showed an effect of zakat on the welfare of muzakki (r) of 0.660 percent. The regression line equation with a value of Y = 1.199 + 0.689X means that there is a positive influence between zakat and the welfare of muzakki of 0.689. If you want to improve welfare, muzakki must increase the quantity in zakat; the probability value shows a significant value of 0.019. The considerable value is 0.019 < 0.05, so H1 is accepted.